Building bridges: Connecting sport marketing and critical social science research - Evans, Zachary Charles Taylor; Gee, Sarah; Eddy, Terry (Frontiers in Sports and Active Living, 2022)
Recently, sport management scholars have called for researchers to critically evaluate the ways in which research questions and resulting contributions truly disrupt what is known, how it is known, why it is important to know, and for whom. Historically, sport marketing research has adapted traditional research approaches from the parent marketing discipline to sport. Yet, sport is a constantly evolving social and cultural phenomenon and a reliance on conventional theories, concepts, and methods can serve to crystalize the discourse in sport marketing in ways that may limit knowledge production. Responding to this call, we believe that sport marketing research has much to gain from engaging with critical social science assumptions, worldviews, and perspectives to examine complex issues in sport. We position this paper as a starting point for advancing the field of sport marketing in meaningful and impactful ways by offering two research propositions, each accompanied by four actional recommendations. We employ a particular focus on the marketing campaigns that activate and promote corporate partnerships in sport to frame our two propositions, which discuss (1) consumer culture theory and (2) the circuit of culture as two important frameworks that begin to build bridges between sport marketing and critical social science.